Influence Of Quality Management Practices On Service Quality Of Facilities Management Mediated By Outsourcing Service Provider Capability - Wang Man, Wah Conny (2022)
This study aims to examine the influence of quality management practices on service quality of facilities management mediated by outsourcing service provider capability. Hong Kong is one of the high-density cities in the world. Due to high-density population with limited space, most of the Hong Kong people lived in crowd buildings with sophisticated facilities. Since the rapid economic boost, Hong Kong properties become the high valuable assets. These factors are the root causes of the demand in high service quality of Hong Kong facilities management companies. Facilities management companies widely adopted quality management practices (strategic planning, customer focus, process management, and supplier management) to supervise the outsourcing service provider capability who served the customers to achieve service quality.